O2A.5 Agricultural exposures and risk of NHLs, by subtypes: results from the agriculture and cancer (AGRICAN) cohort. (April 2019) - Busson, Amandine; Tual, Séverine; Boulanger, Mathilde; Renier, Marine; Pons, Romain; Piel, Clément; Pouchieu, Camille; Perrier, Stéphanie; Levêque-Morlais, Noémie; ,; Guizard, Anne-Valérie; Monnereau, Alain; et al.
Abstract : Purpose: Several studies and meta-analyses demonstrated that farmers have an excess risk of Non-Hodgkin Lymphomas (NHL), including Multiple Myeloma (MM). It has been suggested that pesticides could explain these results. Therefore circumstances of pesticide exposures (on crops, seeds or animals) and other farming tasks need to be explored in relation to NHL risk overall and major subtypes. From the large cohort of French farmers AGRICAN, we assessed the risk of NHL by subtypes (1) compared to the general population and (2) among farmers to identify the farm activities and tasks linked to NHLs subtypes. Methods: AGRICAN cohort enrolled more than 1 80 000 adults registered with the Mutualité Sociale Agricole, from 11 areas. Incident NHLs cases were identified by individual cross linkage with cancer registries from enrolment (2005–2007) to 2013. Lifetime work on 13 crops and 5 types of animals and the tasks performed (with duration and size information) were collected by enrollment questionnaire. Standardized incidence ratios (SIR) were calculated. Associations between NHLs and crops, animals and specific tasks were analyzed using Cox models. Results: 1, 133 NHL incident cases were identified (269 MM, 244 chronic lymphocytic leukemia and small lymphocytic lymphoma (CLL-SLL), and 190 diffuse large B-cell lymphoma (DLBCL)). Increased risks were observed for NHL overall and MM (SIR=1.05, and SIR=1.23, respectively). Positive associations were observed with exposure to pesticides i) on crops: DLBCL (grassland), MM (corn, wheat/barley and potato), CLL-SLL (corn, wheat/barley and vineyard) and DLBCL (tobacco), ii) in seed treatment: in CLL-SLL (sunflower, wheat/barley) and in MM (wheat/barley, corn) and iii) for use on animals (MM). Other tasks were linked to NHL risk: hay making (LDGCB) and harvesting corn (MM) and wheat/barley (CLL-SLL). Conclusion: Our results supports the role of pesticide exposure on NHL risk, not only on crops. Moreover, specific associations according to NHLs subtypes were observed.